Pengembangan Bahan Ajar Ragam Lagu Bermultimedia Menggunakan Model Project-Based Learning di Kelas IV Sekolah Dasar - Arzul, Windy Anisa; Desyandri, Desyandri (Universitas Negeri Padang, 2024)
This research is motivated by the fact that there is a lack of innovation in teaching materials that use technology in Music Arts in class IV elementary schools. This research aims to produce multimedia-assisted teaching materials using the Project Based Learning (PjBL) model with a Blended Learning system that is valid, practical and effective for application to the learning process. The type of research used is development research (R&D) with the ADDILE model which consists of five stages: analysis, design, development, implementation and evaluation. The subjects of this research were class IV student students at SDN 14 Tanjung Beringin, Pasaman Regency. Data from this research were obtained from validation sheets, practicality sheets and pretest-posttest scores. The results of the validation sheet for material experts were 89.58%, language experts 100%, and media experts 90.62% in the very valid category. Meanwhile, the teacher response practicality sheet was 98% and the student response sheet was 100% with very practical categories. The use of multimedia-assisted teaching materials increases student learning outcomes based on pretest-posttest scores from 74% to 94%. Thus, it can be concluded that multimedia-assisted teaching materials are very valid and very practical to use during the learning process.